Preparation process of nano-silver composite conductive adhesive

By adopting the nano-silver composite conductive adhesive preparation process in the conductive adhesive, the existing conductive adhesive has solved the problem of high silver content and poor particle overlap, and the improvement of electrical conductivity and thermal conductivity and cost and reliability have been achieved.

CN119614124APending Publication Date: 2025-03-14JIANGSU TELILAN COATING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937060.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When existing conductive glues improve electrical conductivity and thermal conductivity, the high silver content leads to high raw material costs, and the overlapping improvement space between micron-scale silver powder particles is limited, affecting product reliability.

Method used

The nano-silver composite conductive adhesive preparation process is adopted, and the nano-silver powder and ordinary silver powder are dispersed with other components at high speed and grinding with three rollers to form a uniformly dispersed nano-silver composite conductive adhesive.

Benefits of technology

It significantly improves electrical and thermal conductivity, reduces raw material costs, and improves product reliability through uniformly dispersed nano-silver powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614124A_ABST
    Figure CN119614124A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation process of a nano-silver composite conductive adhesive. The nano-silver composite conductive adhesive comprises the following components in parts by weight: 100 parts of epoxy resin, 50-60 parts of a curing agent, 1-3 parts of an accelerant, 1-5 parts of a coupling agent, 1-3 parts of a performance additive, 1-5 parts of gaseous silicon, 100-200 parts of a diluent, 100-200 parts of nano-silver powder and 600-700 parts of common silver powder. According to the preparation process of the nano-silver composite conductive adhesive, the intermediate and the intermediate added with the two silver powder are subjected to three-roller grinding through three-time high-speed uniform stirring and simultaneous first-time stirring and last-time stirring, the grinding fineness is relatively fine, the nano-silver powder can be uniformly dispersed in a system, and the huddling phenomenon is avoided. And after a certain proportion of nano silver powder is introduced into the conductive adhesive with the same silver content, the electrical conductivity and the thermal conductivity are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive adhesives, and in particular to a preparation process of nano silver composite conductive adhesive. Background Art

[0002] Conductive adhesive is often used as a semiconductor device chip bonding material. Conductive adhesive usually increases the silver content to improve electrical conductivity and thermal conductivity. For example, the volume resistivity of a conductive adhesive with 75% silver content is 1.0×10 -4 hm.c, thermal conductivity is 3W / mK@RT. However, the high silver content leads to high raw material costs, and the silver powder particles are at the micron level, so there is a lot of room for improvement in the overlap between particles to improve product reliability.

[0003] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0004] In view of the deficiencies in the prior art, the embodiment of the present invention discloses a process for preparing a nano-silver composite conductive adhesive.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A process for preparing a nano silver composite conductive adhesive, the nano silver composite conductive adhesive comprising the following components in parts by weight: 100 parts of epoxy resin, 50-60 parts of curing agent, 1-3 parts of accelerator, 1-5 parts of coupling agent, 1-3 parts of modification auxiliary agent, 1-5 parts of gas silicon, 100-200 parts of diluent, 100-200 parts of nano silver powder, and 600-700 parts of common silver powder;

[0007] The preparation process of the nano silver composite conductive adhesive comprises the following steps: firstly, components other than nano silver powder and common silver powder are sequentially added into a container, dispersed evenly at high speed, and then subjected to three-roll grinding to obtain an intermediate; nano silver powder is then added into the uniformly mixed intermediate, dispersed evenly at high speed, and finally common silver powder is added, dispersed evenly at high speed, and then subjected to three-roll grinding to obtain the nano silver composite conductive adhesive.

[0008] The further technical solution is that the epoxy resin is a phenolic epoxy resin and a bisphenol F epoxy resin, and the ratio of the phenolic epoxy resin to the bisphenol F epoxy resin is 6:4. The benzene ring structure in the phenolic epoxy resin can improve the rigidity of the nano-silver composite conductive adhesive after curing and has good heat resistance, and the bisphenol F epoxy resin has a low viscosity, which is conducive to the dispersion of nano-silver powder.

[0009] The further technical solution is that the curing agent is a DDS curing agent, and the nano silver composite conductive adhesive has a high adhesive density after curing. The accelerator is an imidazole accelerator, and a small amount of addition can reduce the curing temperature and accelerate the curing reaction rate. The coupling agent is a silane coupling agent, and a small amount of addition can improve the adhesion between the nano silver composite conductive adhesive and the substrate interface.

[0010] A further technical solution is that the modification auxiliary agent is BYKANTI-TERRA-204, and a small amount of addition can significantly improve the dispersibility of all silver powders.

[0011] A further technical solution is that the diluent is an epoxy active diluent, which is used to adjust the viscosity of the entire system.

[0012] Its further technical solution is that the average size of the nano silver powder is 200nm, and the spherical nano silver powder of Zhongyouyouke is used; the average particle size of the ordinary silver powder is 2-3um, and the flaky silver powder of Guoyin is used; the ratio of nano silver powder to ordinary silver powder is 1:5.

[0013] A further technical solution is that the gas silicon adopts hydrophobic gas phase silica R972, which can prevent sedimentation and improve thixotropy.

[0014] Its further technical solution is that each high-speed dispersion speed is 1000rpm / min, the time is 2min, and it is repeated 3 times; during the first three-roll grinding, the gap between the front roller of the three-roll grinder is 10um, and the gap between the rear roller is 5um, and it is repeated 5 times, and the grinding fineness is less than 5um; during the second three-roll grinding, the gap between the front roller of the three-roll grinder is 20um, and the gap between the rear roller is 10um, and it is repeated 5 times, and the grinding fineness is less than 10um.

[0015] The further technical solution is that the volume resistivity of the prepared nano silver composite conductive adhesive is 5.0×10 - 5 Ohm.cm, thermal conductivity 4W / mK@RT.

[0016] The beneficial effects of the embodiments of the present invention are as follows:

[0017] (I) The preparation process of a nano-silver composite conductive adhesive of the present invention is to stir evenly three times at high speed, and at the same time, the intermediate and the intermediate after adding two kinds of silver powder are respectively subjected to three-roll grinding in the first and last stirring, and the grinding fineness is relatively fine, so that the nano-silver powder can be evenly dispersed in the system without agglomeration. And after introducing a certain proportion of nano-silver powder into the conductive adhesive with the same silver content, the electrical conductivity and thermal conductivity are greatly improved.

[0018] (ii) Further, the epoxy resin is a phenolic epoxy resin and a bisphenol F epoxy resin. The benzene ring structure in the phenolic epoxy resin can improve the rigidity of the nano-silver composite conductive adhesive after curing and has good heat resistance. The bisphenol F epoxy resin has a low viscosity, which is conducive to the dispersion of nano-silver powder. Adding DDS curing agent can increase the adhesive density of the nano-silver composite conductive adhesive after curing. Adding a small amount of imidazole accelerator can reduce the curing temperature and accelerate the curing reaction rate. Adding a small amount of silane coupling agent can improve the adhesion between the nano-silver composite conductive adhesive and the substrate interface. Adding a small amount of modification additive can significantly improve the dispersibility of silver powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flow chart of a process for preparing a nano-silver composite conductive adhesive.

[0020] Figure 2 This is a photograph of the cross section of the conductive adhesive of the present invention after curing, magnified 100 times.

[0021] Figure 3 This is a photograph of the cross section of the conductive adhesive of the present invention after curing, magnified 2000 times.

[0022] Figure 4 This is a photo of the cross section of an ordinary micron-sized conductive adhesive after curing, magnified 100 times.

[0023] Figure 5 This is a photograph of the cross section of the conductive adhesive of the present invention after curing, magnified 2000 times. DETAILED DESCRIPTION

[0024] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings.

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the device proposed by the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. According to the following description, the advantages and features of the present invention will be clearer. It should be noted that the accompanying drawings adopt a very simplified form and use non-precise proportions, which are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention. In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, please refer to the accompanying drawings. It should be noted that the structure, proportion, size, etc. illustrated by the accompanying drawings of this specification are only used to match the content disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no technical substantive significance. Any modification of the structure, change of the proportional relationship or adjustment of the size, without affecting the effect that the present invention can produce and the purpose that can be achieved, should still fall within the scope of the technical content disclosed by the present invention.

[0026] First embodiment:

[0027] A process for preparing a nano-silver composite conductive adhesive, wherein the nano-silver composite conductive adhesive comprises the following components in parts by weight:

[0028] 100 parts of epoxy resin, 55 parts of curing agent, 2 parts of accelerator, 3 parts of coupling agent, 2 parts of modification aid, 3 parts of gas silicon, 190 parts of diluent, 130 parts of nano silver powder, and 650 parts of ordinary silver powder.

[0029] The epoxy resin is phenolic epoxy resin and bisphenol F epoxy resin, and the ratio of phenolic epoxy resin to bisphenol F epoxy resin is 6:4.

[0030] The curing agent is DDS curing agent. The accelerator is 2-ethyl-4-methylimidazole. The coupling agent is γ-glycidyloxypropyl triethoxysilane. The modification agent is BYKANTI-TERRA-204. The average size of the nano silver powder is 200nm, and the spherical nano silver powder of Zhongyouyouke is used. The average particle size of the ordinary silver powder is 2-3um, and the flake silver powder of Guoyin is used. The ratio of nano silver powder to ordinary silver powder is 1:5. The gas silicon uses hydrophobic gas phase silica R972.

[0031] The preparation process of nano silver composite conductive adhesive includes the following steps:

[0032] First, add the components except nano silver powder and common silver powder into the container in sequence, disperse them evenly at high speed, and then grind them with three rollers to obtain an intermediate. Then add nano silver powder to the mixed intermediate and disperse them evenly at high speed. Finally, add common silver powder and disperse them evenly at high speed, and then grind them with three rollers to obtain a nano silver composite conductive adhesive.

[0033] Specifically, the high-speed dispersion speed is 1000 rpm / min each time, the time is 2 minutes, and it is repeated 3 times. During the first three-roll grinding, the gap between the front roller of the three-roll grinder is 10um, and the gap between the rear roller is 5um. This is repeated 5 times, and the grinding fineness is less than 5um. During the second three-roll grinding, the gap between the front roller of the three-roll grinder is 20um, and the gap between the rear roller is 10um. This is repeated 5 times, and the grinding fineness is less than 10um.

[0034] Second embodiment:

[0035] A process for preparing a nano-silver composite conductive adhesive, wherein the nano-silver composite conductive adhesive comprises the following components in parts by weight:

[0036] 100 parts of epoxy resin, 50 parts of curing agent, 1 part of accelerator, 1 part of coupling agent, 3 parts of modification aid, 1 part of gas silicon, 150 parts of diluent, 100 parts of nano silver powder, and 600 parts of ordinary silver powder.

[0037] The epoxy resin is phenolic epoxy resin and bisphenol F epoxy resin, and the ratio of phenolic epoxy resin to bisphenol F epoxy resin is 6:4.

[0038] The curing agent is DDS curing agent. The accelerator is 2-ethyl-4-methylimidazole. The coupling agent is γ-glycidyloxypropyl triethoxysilane. The modification agent is BYKANTI-TERRA-204. The average size of the nano silver powder is 200nm, and the spherical nano silver powder of Zhongyouyouke is used. The average particle size of the ordinary silver powder is 2-3um, and the flake silver powder of Guoyin is used. The gas silicon uses hydrophobic gas phase silica R972.

[0039] The preparation process of nano silver composite conductive adhesive includes the following steps:

[0040] First, add the components except nano silver powder and common silver powder into the container in sequence, disperse them evenly at high speed, and then grind them with three rollers to obtain an intermediate. Then add nano silver powder to the mixed intermediate and disperse them evenly at high speed. Finally, add common silver powder and disperse them evenly at high speed, and then grind them with three rollers to obtain a nano silver composite conductive adhesive.

[0041] Specifically, the high-speed dispersion speed is 1000 rpm / min each time, the time is 2 minutes, and it is repeated 3 times. During the first three-roll grinding, the gap between the front roller of the three-roll grinder is 10um, and the gap between the rear roller is 5um. This is repeated 5 times, and the grinding fineness is less than 5um. During the second three-roll grinding, the gap between the front roller of the three-roll grinder is 20um, and the gap between the rear roller is 10um. This is repeated 5 times, and the grinding fineness is less than 10um.

[0042] Third embodiment:

[0043] A process for preparing a nano-silver composite conductive adhesive, wherein the nano-silver composite conductive adhesive comprises the following components in parts by weight:

[0044] 100 parts of epoxy resin, 60 parts of curing agent, 3 parts of accelerator, 5 parts of coupling agent, 1 part of modification aid, 5 parts of gas silicon, 200 parts of diluent, 200 parts of nano silver powder, and 700 parts of ordinary silver powder.

[0045] The epoxy resin is phenolic epoxy resin and bisphenol F epoxy resin, and the ratio of phenolic epoxy resin to bisphenol F epoxy resin is 6:4.

[0046] The curing agent is DDS curing agent. The accelerator is 2-ethyl-4-methylimidazole. The coupling agent is γ-glycidyloxypropyl triethoxysilane. The modification agent is BYKANTI-TERRA-204. The average size of the nano silver powder is 200nm, and the spherical nano silver powder of Zhongyouyouke is used. The average particle size of the ordinary silver powder is 2-3um, and the flake silver powder of Guoyin is used. The gas silicon uses hydrophobic gas phase silica R972.

[0047] The preparation process of nano silver composite conductive adhesive includes the following steps:

[0048] First, add the components except nano silver powder and common silver powder into the container in sequence, disperse them evenly at high speed, and then grind them with three rollers to obtain an intermediate. Then add nano silver powder to the mixed intermediate and disperse them evenly at high speed. Finally, add common silver powder and disperse them evenly at high speed, and then grind them with three rollers to obtain a nano silver composite conductive adhesive.

[0049] Specifically, the high-speed dispersion speed is 1000 rpm / min each time, the time is 2 minutes, and it is repeated 3 times. During the first three-roll grinding, the gap between the front roller of the three-roll grinder is 10um, and the gap between the rear roller is 5um. This is repeated 5 times, and the grinding fineness is less than 5um. During the second three-roll grinding, the gap between the front roller of the three-roll grinder is 20um, and the gap between the rear roller is 10um. This is repeated 5 times, and the grinding fineness is less than 10um.

[0050] The first comparison

[0051] The nano silver powder in the first embodiment is replaced with ordinary silver powder, and ordinary silver powder is added to the uniformly mixed intermediate, dispersed uniformly at high speed, and then three-roll grinding is performed to obtain a conductive adhesive. The rest is the same as the first embodiment.

[0052] The performance of the nano silver composite conductive adhesives prepared in the first embodiment, the second embodiment, the third embodiment and the first comparative example was tested. The test results are shown in Table 1.

[0053] Table 1

[0054]

[0055]

[0056] Among them, the test method is as follows:

[0057] Volume resistivity:

[0058] The material was made into a sample with a length of L = 5 cm, a width of b = 0.5 cm, and a thickness of d = 0.003 cm. The volume resistance R was tested using a Keysight digital multimeter Keysight 34461A, and the resistivity was calculated using the formula as follows:

[0059] ρ = Rbd / L;

[0060] ρ is the sample volume resistivity, R is the sample volume resistance, b is the sample width, d is the sample thickness, and L is the sample length. The sample length, width, and thickness can be determined by yourself.

[0061] Thermal conductivity:

[0062] Thermal conductivity = thermal conductivity * specific heat * density.

[0063] The thermal conductivity is measured by laser scattering method. The material is made into a sample of a certain shape and thickness, both sides of the sample are polished, and the density and specific heat capacity of the sample are tested. Then, a uniform carbon black layer is sprayed on both sides of the sample, and then the test is carried out according to the test procedure. The test scans three points, and then Cowan+ pulse correction is performed to obtain relevant test results.

[0064] Specific heat: The basic principle of the sapphire method for measuring specific heat capacity is to use a differential scanning calorimeter (DSC) for testing. The DSC tester calculates the specific heat capacity of the sample by measuring the difference in heat flow between the sample and the reference material. Specifically, the sapphire method uses a reference material such as sapphire as a sample for measurement under the same conditions, and then calculates the specific heat capacity of the unknown sample from the known specific heat capacity of sapphire. This method requires the subtraction of a blank curve to compensate for any asymmetry of the measurement system.

[0065] The specific steps of measuring specific heat capacity by sapphire method are as follows:

[0066] Isothermal stage: First, the sample is kept at the starting temperature for 5 to 10 minutes.

[0067] Heating stage: The sample is then heated from the starting temperature to the ending temperature at a heating rate of 10 K / min or 20 K / min.

[0068] Isothermal stage: Finally, the sample is kept at the final temperature for 5 to 10 minutes.

[0069] Density: The density of the cured silver paste is measured by the drainage method.

[0070] Figure 2 This is a photograph of the cross section of the conductive adhesive of the present invention after curing, magnified 100 times. Figure 3 This is a photograph of the cross section of the conductive adhesive of the present invention after curing, magnified 2000 times. Figure 4 This is a photo of the cross section of an ordinary micron-sized conductive adhesive after curing, magnified 100 times. Figure 5 This is a photograph of the cross section of the conductive adhesive of the present invention after curing, magnified 2000 times. Figure 2 , Figure 3 It can be seen that the black shadow part is relative to Figure 4 and Figure 5 Reduced, the overlap between silver and silver is closer. Figure 4 and Figure 5 It can be seen that there are many gaps between the silver powders, such as the black shadow areas.

[0071] In summary, the formulation and preparation process of the present invention can make the nano silver powder evenly dispersed in the system, and after introducing a certain proportion of nano silver powder into the conductive glue with the same silver content, the electrical conductivity and thermal conductivity can be greatly improved.

[0072] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A process for preparing a nano-silver composite conductive adhesive, characterized in that: The nano silver composite conductive adhesive comprises the following components in parts by weight: 100 parts of epoxy resin, 50-60 parts of curing agent, 1-3 parts of accelerator, 1-5 parts of coupling agent, 1-3 parts of modification aid, 1-5 parts of gas silicon, 100-200 parts of diluent, 100-200 parts of nano silver powder, 600-700 parts of ordinary silver powder; The nano silver composite conductive adhesive preparation process comprises the following steps: First, the components except nano silver powder and common silver powder are sequentially added into a container, dispersed evenly at high speed, and then three-roll grinding is performed to obtain an intermediate; nano silver powder is then added into the mixed intermediate and dispersed evenly at high speed, and finally common silver powder is added and dispersed evenly at high speed, and then three-roll grinding is performed to obtain a nano silver composite conductive adhesive.

2. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The epoxy resin is a phenolic epoxy resin and a bisphenol F epoxy resin, and the ratio of the phenolic epoxy resin to the bisphenol F epoxy resin is 6:

4.

3. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The curing agent is a DDS curing agent; the accelerator is an imidazole accelerator; and the coupling agent is a silane coupling agent.

4. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The modification aid is BYKANTI-TERRA-204.

5. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The diluent is an epoxy reactive diluent.

6. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The nano silver powder has an average size of 200nm, and uses spherical nano silver powder from Zhongyouyouke; the ordinary silver powder has an average particle size of 2-3um, and uses flaky silver powder from Guoyin; the ratio of nano silver powder to ordinary silver powder is 1:

5.

7. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The gas silicon adopts hydrophobic gas phase silica R972.

8. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: Each high-speed dispersion speed is 1000rpm / min, the time is 2min, and it is repeated 3 times; during the first three-roll grinding, the gap between the front roller of the three-roll grinder is 10um, and the gap between the rear roller is 5um. This is repeated 5 times, and the grinding fineness is <5um; during the second three-roll grinding, the gap between the front roller of the three-roll grinder is 20um, and the gap between the rear roller is 10um. This is repeated 5 times, and the grinding fineness is <10um.

9. The process for preparing the nano silver composite conductive adhesive according to claim 1, characterized in that: The volume resistivity of the prepared nanosilver composite conductive adhesive is 5.0×10 -5 Ohm.cm, thermal conductivity is 4W / mK@RT.